An inadvertent subarachnoid injection reversed by cerebrospinal fluid lavage for the treatment of chronic low back pain: A case report. Issue 6 (February 2019) - Sun, Xiaodi; Liu, Shijiang; Liu, Cunming; Xu, Jijun; Sun, Jie; Pan, Yinbing
Abstract: Rationale: We present a case of high spinal anesthesia after inadvertent injection of local anesthetics and corticosteroids into the subarachnoid space during attempted epidural injection. Cerebrospinal fluid (CSF) lavage is a suitable method for treatment. Patient concerns: A 45-year-old woman presented with posterior thigh, leg, and ankle pain for >6 months and was treated with epidural injection. Five minutes after the third time of epidural injection, the patient complained loss of sensation and muscle strength in the lower extremities and abdominal area. Diagnoses: A high spinal anesthesia was confirmed by the patient loss of sensation and muscle strength in the lower extremities and abdominal area. Interventions: CSF lavage was performed for treatment. Outcomes: After CSF lavage, the patient gradually returns to normal sensory and motor functions of lower limbs. On the fourth day, the patient sensed her physical function restoring gradually and was discharged uneventfully. At 4-month follow-up, the patient could have normal activities without obvious subsequent complications and any pain. Lessons: We conclude that CSF lavage could be a helpful maneuver to clear lidocaine and betamethasone and avoid potential nerve damage caused by an unintentional intrathecal injection during an epidural injection for the treatment of chronic low back pain.